National Wheat and Maize Flour Fortification Standards and Their Comparison with International Guidelines in Countries with Mandatory Fortification (P22-001-19). (13th June 2019) - Bobrek, Katya; Broersen, Britt; Aburto, Nancy; Garg, Aashima; Serdula, Mary; Velazquez, Filiberto Beltran; Wong, Eugene; Pachon, Helena
Abstract: Objectives: Compare national wheat and maize flour standards to World Health Organization (WHO) fortification guidelines in countries with mandatory fortification. Methods: Seventy-three countries' grain availability, flour extraction rate, flour standards (with fortification compounds and nutrient levels) and mass fortification of other foods were obtained from databases and country contacts. For each nutrient, standards were compared with recommendations, specifically, presence of a compound that is in guidelines was noted (yes/no), and nutrient levels in standards were classified as lower than, equal to, or higher than those suggested by WHO. When a nutrient in flour was categorized as "lower than" in a particular standard and if another food (e.g., rice, oil, milk) was mass fortified with the same nutrient, the classification was changed to "less than recommendation and included in other mass fortified food". Results: At least 63% of standards included one or more recommended compounds for all nutrients in standards for wheat flour alone (iron, folic acid, vitamin A, zinc, vitamin B12, ), wheat and maize flour together (iron, folic acid, vitamin A, zinc, vitamin B12) and maize flour alone (thiamin, riboflavin, niacin, pyridoxine); no country included pantothenic acid in its maize flour standard. For folic acid, vitamin A, thiamin, riboflavin, niacin and pyridoxine, >50% of standards (1) met or exceeded WHO suggested levels, or (2) were lower than suggested levels and another food was mass fortified with the specific nutrient in the country. For iron, zinc and vitamin B12, <50% of standards met (1) or (2). Conclusions: Iron, zinc and vitamin B12 may require the most attention in national wheat and maize flour fortification standards. Funding Sources: No external funding received for conduct of this study.